FRI0178 Estimated Medical Expenditures among Patients with Rheumatoid Arthritis Undergoing Treatment with Tofacitinib, an Oral Janus Kinase Inhibitor. (10th June 2014) - Rendas-Baum, R.; Kosinski, M.; Singh, A.; Mebus, C.; Wilkinson, B.; Riese, R.; Wallenstein, G.
Abstract : Background: Tofacitinib is a novel, oral Janus kinase inhibitor for the treatment of rheumatoid arthritis. Phase (P) 3 studies demonstrated tofacitinib is effective and has a manageable safety profile at both 5 and 10 mg twice-daily (BID) doses. Objectives: To assess, using post-hoc analyses of P3 data, whether active treatment could affect monthly medical expenditure (MME) compared with placebo. Methods: Data from patients with an inadequate response (IR) to methotrexate (MTX) or TNF inhibitors (TNFi) receiving tofacitinib 5 or 10 mg BID, or adalimumab (ORAL Standard only), in combination with methotrexate, were assessed from two randomised P3 studies (ORAL Standard, NCT00853385 [MTX-IR] and ORAL Step, NCT00960440 [TNFi-IR]). Differences across treatment groups in estimated MME were evaluated using a longitudinal model. A total of three models were run for each study, each with one of the following variance–covariance structures: 1) unstructured, 2) auto-regressive of order 1 and 3) compound symmetry. The final variance–covariance structure was selected based on Akaike's Information Criteria. Results: Estimated MME by treatment group for MTX-IR in ORAL Standard is presented in Fig. 1a . By Month 1 mean MME was significantly lower in the active treatment groups when compared with placebo; the MME was decreased −$89 for the tofacitinib 10 mg BID group compared with an increase of $70 in both the tofacitinib 5 mg BID and adalimumab groups. During the placebo-controlled phase of ORAL Step, estimated MME by treatment group for TNFi-IR decreased from baseline to Month 1. Between Month 1 and Month 3 the MME of the placebo group increased but declined further in the two active tofacitinib treatment groups (Fig. 1b ). By Month 3 the reduction in MME was over $100 greater in each of the two tofacitinib groups when compared with placebo. Conclusions: Tofacitinib is expected to have a positive impact on medical expenditure over time compared with placebo. Acknowledgements: Editorial assistance was provided by Mark Walker PhD, of Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: R. Rendas-Baum: None declared, M. Kosinski: None declared, A. Singh Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., C. Mebus Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., B. Wilkinson Shareholder of: Pfizer Inc., Employee of: fizer Inc., R. Riese Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., G. Wallenstein Shareholder of: Pfizer Inc., Employee of: Pfizer Inc. DOI: 10.1136/annrheumdis-2014-eular.2476